Factors Associated to Subjective Wellbeing in Older Adults [Fatores Associados Ao Bem-Estar Subjetivo Dos Idosos] [Factores Asociados Al Bienestar Subjetivo en Los Adultos Mayores] - Oyanedel-Sepulveda, J (Universidade Federal de Santa Catarina, 2017)
Objective: identify the factors associated with subjective wellbeing in older adults. Method: analytical, cross-sectional study developed in Chile. The sample consisted of 20,351 seniors, who answered a question on overall life satisfaction in the National Socio-Economic Survey, 2011. Subjective wellbeing was correlated with health, demographic and social indicators. Comparisons of averages, correlations and regressions were applied using the software Statistical Package for the Social Sciences 20. Results: life satisfaction was associated with increased age; being male; participation in social organizations; being married or living as a couple; having higher education level; higher income; good perceived health status and better health care. Conclusion: according to the age and income predictors, it can be concluded that, over the years, life satisfaction is reinforced, but in combination with adequate perceived health and income, which permit an excellent quality of life. © 2017, Universidade Federal de Santa Catarina. All rights reserved.